Validity and Reliability Survey of Mathematical Reasoning Ability of Senior High School Students Using Statistical Applications - Triasti, Dinda; Farhanah, Qathrunnada; Santosa, Sofia Rengganis; Faradillah, Ayu; Ulfah, Syafika (Pattimura University, 2024)
In Indonesia, students' reasoning ability is still very low, especially in mathematical reasoning ability. It was found that the data of mathematical reasoning ability test results of class X students where only 47.22% reached the minimum learning completeness. Reasoning ability also plays an important role in the process of thinking creatively, logically, and systematically so that students can conclude solutions from several known facts as well as proof of mathematical statements, find new ideas, overcome challenges in solving mathematical problems, and reduce dependence on memorization. This study aims to determine the validity and reliability in mathematical reasoning ability of high school students using two statistical applications, namely SPSS and Winstep. The research method used is a quantitative research method with a survey approach, which has a total of 252 respondents from class X high school students in Jakarta. The results of the validity test research using SPSS have 6 valid items so that they are in accordance with the criteria. While the results of the validity test using Winstep there are seven items that do not match the three, and there are twenty-nine items that only meet one requirement, so 154 items must be maintained because they are fulfilled. Meanwhile, the results of reliability calculations using SPSS and Winstep obtained the results (α = 0,74). By using two different statistical applications, namely SPSS and Winstep, it can be stated that the results of the mathematical reasoning ability test have been declared valid and reliable.